Podcast y el territorio de la accesibilidad cultural : reflexiones desde el escenario brasileño - Pinheiro, Elton Bruno Barbosa (2021)
The present work aims to reflect on the possibilities of making podcast content accessible to a sensory diverse audience, especially the deaf and blind community. As axes of theoretical articulation, the field of cultural accessibility studies and the regulatory framework of the area are compared with an approach to the characteristics and functions of radio language, aiming the contextualization of the accessibility alternatives for the podosphere. Methodologically, it uses resources from the literature review and comprehensive interviews on the topic of cultural accessibility. As a result, it is emphasized that podcasts are forms of expression of radio language that can and should be made accessible and present contributory strategies to this process, such as transcriptions, descriptive and creative subtitling, audio description, use of Brazilian Sign Language, links, hashtags and alternative texts.